Implementation and evaluation of a standardized performance profile intervention with collegiate athletes: A comparison of the original and revised techniques. Issue 3 (4th May 2022) - Castillo, Elmer A.; Bird, Matthew D.; Chow, Graig M.
Abstract: Performance profiling is a theory-driven technique commonly employed by sport psychology professionals to enhance various psychological outcomes within athletes and teams. Over time, empirical and anecdotal evidence have advocated the applied use of this technique and several adaptations of the original profiling procedure have emerged. The purpose of this study was to examine the impact of the original and revised performance profile (PP) techniques compared to a didactic active control condition on self-awareness, intrinsic motivation, basic psychological need satisfaction, and commitment. A standardized intervention protocol was developed for each performance profiling procedure and utilized to guide implementation of the interventions. Using a randomized design, 117 collegiate athletes from different sports were allocated to a(n) original PP ( n = 41), revised PP ( n = 42), or didactic PP ( n = 34) condition to examine the pre-post impacts of a single session delivered in a team setting. Two-way mixed ANOVAs and MANOVAs were used to analyze the pre to post changes across intervention conditions for the outcome variables. Paired comparisons using two-way mixed ANOVAs were used to determine which intervention was most effective. Results revealed that self-awareness significantly increased for the original and revised condition, however, no differences in improvement were seen between the groups. Furthermore, those in the original group reported significantly higher scores on numerous intrinsic motivation subscales from pre to post intervention, while significantly elevated scores for commitment were reported in the revised condition. Lay summary: Performance profiling is an assessment tool used by athletes, coaches, and sport psychology professionals to help identify athletes' strengths and weaknesses. The original and revised versions of the technique may influence different psychological constructs. Implications for practice: Sport psychology professionals should carefully consider which performance profile they implement in practice as the original and revised versions influence different psychological constructs. Practitioners might contemplate, from their perspective, the usefulness of data derived from each performance profiling method, before implementing a version in practice.